Strengthening Laboratory Capabilities in Improving HIV/AIDS and Other Diseases Support in Zimbabwe - Mayavo, Crossman (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Laboratory services are always overlooked by the governments when it comes to funding, and they are mostly left behind in terms of newer testing technologies, however, in Zimbabwe, there has been a tremendous improvement in laboratory support through the partners and donors. Aims: The objective of the study was to review the progress made in strengthening laboratory capabilities in improving HIV/AIDS and other disease support in Zimbabwe. Methods: This study adopted a qualitative research method based on secondary data collected from laboratory documentation, including websites such as SADCAS. The study focused mainly on laboratories scattered around Zimbabwe, on the improvements made in support of HIV care in Zimbabwe. Results: The results show that there has been a great improvement in terms of laboratory performance and management through support from various donors interested in HIV/AIDS, TB and Malaria. Furthermore, the results show that there are currently 13 public health laboratories accredited to SADCAS, several improvements in employee support, and new technologies are being employed throughout the Zimbabwean laboratories for both HIV and TB care. Additionally, the laboratory information system is functional and now helps to send laboratory results to clinics and patients for patient management by all the clinics and hospitals. Conclusion: However, concerns regarding reliance on and the sustainability of these partnerships remain a challenge if they sever ties with the laboratory services, as the funding from the government is not adequate to support the laboratory’s full independence. As for the policy makers, they can help to improve the funding gaps to enable sustainability in the long run so that the gains acquired will not go to waste if the donors and partners decide otherwise, as is happening with USAID and PEPFAR funding.